2015
DOI: 10.1109/access.2015.2471178
|View full text |Cite
|
Sign up to set email alerts
|

Cognition-Based Networks: A New Perspective on Network Optimization Using Learning and Distributed Intelligence

Abstract: IEEE Access\ud Volume 3, 2015, Article number 7217798, Pages 1512-1530\ud Open Access\ud Cognition-based networks: A new perspective on network optimization using learning and distributed intelligence (Article)\ud Zorzi, M.a , Zanella, A.a, Testolin, A.b, De Filippo De Grazia, M.b, Zorzi, M.bc \ud a Department of Information Engineering, University of Padua, Padua, Italy \ud b Department of General Psychology, University of Padua, Padua, Italy \ud c IRCCS San Camillo Foundation, Venice-Lido, Italy \ud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(67 citation statements)
references
References 99 publications
0
67
0
Order By: Relevance
“…For each time, we create a dataset varying the following network and topology parameters: transmit power {0 dBm, 5 dBm, 10 dBm, 15 dBm, 20 dBm}, WiFi transmission channel {1, 6, 11}, number of nodes simultaneously receiving data from the transmitter (from 1 to 4) and distance between the transmitter and the receivers {1 m, 5 m, 10 m}. Finally, for each configuration, we measure the transmission duration of a 100 MB file 3 .…”
Section: A Testbedmentioning
confidence: 99%
See 2 more Smart Citations
“…For each time, we create a dataset varying the following network and topology parameters: transmit power {0 dBm, 5 dBm, 10 dBm, 15 dBm, 20 dBm}, WiFi transmission channel {1, 6, 11}, number of nodes simultaneously receiving data from the transmitter (from 1 to 4) and distance between the transmitter and the receivers {1 m, 5 m, 10 m}. Finally, for each configuration, we measure the transmission duration of a 100 MB file 3 .…”
Section: A Testbedmentioning
confidence: 99%
“…Each configuration of the network has been tested 10 times, and the median of these results has been stored in the dataset, so as to reduce the variability effects of the transmission channels. Note that, although choosing the median of 10 experiments as an input for our algorithms could artificially reduce the level of randomness typical of wireless transmissions, we highlight that the ETA measurements belonging to the same set of experiments only have 2 USB version of ath9k 3 The average size of a music video in full HD (1080p) resolution low standard deviation: a separate paper taking into account all these measurements is currently in preparation. The dataset is thus composed by M = 540 examples.…”
Section: A Testbedmentioning
confidence: 99%
See 1 more Smart Citation
“…Such learning platforms should account for noisy nature of data collection and ensure prediction of what measurements are to be expected. Such network wide M L based cognition platform is proposed in [86]. The authors identified how generative deep neural networks (GDNN) are suited for network wide cognition and full self-organization capability.…”
Section: General Learning Frameworkmentioning
confidence: 99%
“…The neural network is trained to identify how environmental measurements and the status of the network affect the performance experienced on different channels. In [52] [54], where a locating array is used to identify the 5 most influential parameters out of an initial design space of 24 parameters. As such, by applying dimensionality reduction techniques before model creation, the exploration time can significantly be reduced.…”
Section: Challenges Related To Network Optimizationmentioning
confidence: 99%